Research on Digital Mapping Method Based on Complex Terrain. (November 2020) - Zhu, Pengpeng; Cui, Hengle; Zhang, Zipan; Li, Jian; Ding, Xiaopeng
Abstract: Based on UAV low-altitude remote sensing technology and tilt photography technology, combined with highway projects, the UAV operating process, quality inspection and accuracy, and positioning accuracy in the mountainous complex terrain conditions are analyzed, and operating experience is summarized for subsequent navigation. The production provides guidance. At the same time, it also provides a reference for the exploration of digital mapping methods, and lays a theoretical foundation for the research of mapping methods. The combination of mapping methods in complex terrain with high technology is highly innovative.